STRATEGI PENGEMBANGAN UMKM DALAM MENGHADAPI PERSAINGAN DI ERA DIGITAL DI KOTA PONTIANAK - Vera Aryani; Henrian Stiawan, Ika Lusiana Sari (CV. Adiba Aisha Amira, 2025)
This research aims to analyze the development strategy of MSMEs (Micro, Small, and Medium Enterprises) in facing digital era competition in Pontianak City. Using a mixed-method approach, the research was conducted on 375 MSME entrepreneurs through a combination of surveys, in-depth interviews with 20 key informants, observations of 10 MSMEs, and focus group discussions with three stakeholder groups. The results show that the level of digital technology adoption among MSMEs remains at a medium level (40% active, 35% in transition, 25% conventional), with key influencing factors including digital literacy, resource availability, and ecosystem support. MSMEs that have adopted digital technology showed an average revenue increase of 157% and operational efficiency improvements of 25-30%. The research recommends a comprehensive development strategy that includes strengthening digital capacity, facilitating access to technology and infrastructure, developing financing schemes, strengthening collaboration with digital platforms, and developing sustainable assistance systems. The implementation of this strategy requires active collaboration between local government, private sector, academics, and MSME communities in building a supportive digital ecosystem.